Validation of abnormal glucose metabolism associated with Parkinson’s disease in Chinese participants based on 18F-fluorodeoxyglucose positron emission tomography imaging - Jin R (Dove Medical Press, 2018)
Rongbing Jin,1,* Jingjie Ge,2,* Ping Wu,2 Jiaying Lu,2 Huiwei Zhang,2 Jian Wang,3 Jianjun Wu,3 Xianhua Han,2 Weishan Zhang,2 Chuantao Zuo2,4 1Department of Nuclear Medicine, Daping Hospital, Army Medical University, Chongqing 400042, China; 2PET Center, Huashan Hospital, Fudan University, Shanghai 200235, China; 3Department of Neurology, Huashan Hospital, Fudan University, Shanghai 200040, China; 4Institute of Functional and Molecular Medical Imaging, Fudan University, Shanghai 200433, China *These authors contributed equally to this work Purpose: We previously identified disease-related cerebral metabolic characteristics associated with Parkinson’s disease (PD) in the Chinese population using 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) imaging. The present study aims to assess data reproducibility and robustness of the metabolic activity characteristics across independent cohorts. Patients and methods: Forty-eight patients with PD and 48 healthy controls from Chongqing district, in addition to 33 patients with PD and 33 healthy controls from Shanghai district were recruited. Each subject underwent brain 18F-FDG PET/CT imaging in a resting state. Based on the brain images, differences between the groups and PD-related cerebral metabolic activities were graphically and quantitatively evaluated. Results: Both PD patient cohorts exhibited analogous cerebral patterns characterized by metabolic increase in the putamen, globus pallidus, thalamus, pons, sensorimotor cortex and cerebellum, along with metabolic decrease in parieto-occipital areas. Additionally, the metabolic pattern was highly indicative of the disease, with a significant elevation in PD patients compared with healthy controls (p<0.001) in both the derivation (Shanghai) and validation (Chongqing) cohorts. Conclusion: This dual-center study demonstrated the high comparability and reproducibility of PD-related cerebral metabolic activity patterns across independent Chinese cohorts and may serve as an objective diagnostic marker for the disease. Keywords: movement disorders, parkinsonism, disease diagnosis, positron emission tomography, neuroimaging marker, Parkinson’s disease